The Unique Contribution of Past Bullying Experiences to the Presence of Psychosis-Like Experiences in University Students - Zhao, Jie; Lu, Xiao-Hua; Liu, Yuan; Wang, Nan; Chen, Dong-Yang; Lin, Iun-An; Li, Xiao-Hong; Zhou, Fu-Chun; Wang, Chuan-Yue (Frontiers in Psychiatry, 2022)
Objectives Both bullying and psychosis-like experiences (PLEs) have gained much attention in recent years, but their interactions are not fully unraveled. The aim of the current study was to validate the Chinese version of Bullying Scale for Adults (C-BSA), and to investigate whether past bullying experiences independently predict the presence of PLEs in university students. Methods The validity and reliability of the C-BSA were determined in two independent samples. A battery of psychological inventories was also administered to assess the presence of PLEs, maltreatment history in the family, and current depression and anxiety, including the 15-item positive subscale of the community assessment of psychic experiences (CAPE-p15), the Chinese version of the Childhood Trauma Questionnaire (CTQ), Self-Rating Depression Scale (SDS), and Self-Rating Anxiety Scale (SAS). Results In the construction sample (N = 629), a Cronbach's α of 0.921 indicated a good internal consistency of C-BSA. The exploratory factor analysis (EFA) yielded a four-factor model and a three-factor model, and both were verified by using the confirmatory factorial analysis (CFA) in the validation sample (N = 629). The total scores of C-BSA were significantly correlated with that of CTQ, CAPE-p15, SDS, and SAS. Multivariate logistic regression revealed that bullying was associated with 2.0 or 3.7 times of risk for the presence of PLEs (numbers of bullying types < = 3 or > 3, respectively) after controlling for CTQ, SDS, and SAS scores. Conclusions C-BSA has shown good psychometric properties in college students. The contribution of past bullying experiences to the present PLEs seems to be independent of other childhood trauma, current depression, and anxiety.